Myroides cellulitis and bacteremia: A case report. (2021) - Beathard, William A.; Pickering, Aaron; Jacobs, Micah
Abstract: Formerly classified under the genus Flavobacterium, Myroides species are common gram-negative, environmental bacterium ubiquitous in soil and water. While infrequent, infections of human hosts can result in devastating consequences due the bacteria's intrinsic multidrug resistance, particularly in those who are immunocompromised. The pathogenicity and mechanisms for resistance remain poorly understood at this time. The case presented in this report details Myroides bacteremia secondary to a soft tissue infection of the lower extremities and adds to the 60 documented infections to date, of which 15 were also characterized by a similar infection.